A Comparative Study on the Prevalence of Helicobacter pylori Infection in Patients with Central Serous Chorioretinopathy versus a Control Population - Saad EME; Mohammed HEM; Ibrahim MMA; Abdhafez SME; Selim OHS; Tawfik AMR; Abbass AME; Alabshihy MSI; Ayoub AAA; Ghazala AMA; Abdelmaged WKA (Clinical Ophthalmology)
Ehab Mohamed Elsayed Saad,1 Hazem Elbadry Mohammed Mohammed,2 Mohamed Mohamed-Aly Ibrahim,2 Sayed Mostafa Elsayed Abdhafez,2 Omar Hassan Salama Selim,2 Ahmed Mohamed Raafat Tawfik,2 Anas Malek Ebrahim Abbass,2 Mohammed Saad Ibrahim Alabshihy,2 Ahmed Abdelmohsen Ali Ayoub,2 Ahmed Mohamed Ahmed Ghazala,2 Wafaa Kamel Abdelmoneim Abdelmaged3 1Ophthalmology Department, Faculty of Medicine, Benha University, Benha, Egypt; 2Ophthalmology Department, Faculty of Medicine, Al-Azhar University, Cairo, Egypt; 3Internal Department, Faculty of Medicine, Benha University, Benha, EgyptCorrespondence: Ehab Mohamed Elsayed Saad, Ophthalmology Department, Faculty of Medicine, Benha University, Benha, 13511, Egypt, Tel +201008418667, Email ehab.saad@fmed.bu.edu.egPurpose: This study investigates the association between Helicobacter pylori (H. pylori) infection and Central Serous Chorioretinopathy (CSCR) by comparing the prevalence of H. pylori in CSCR patients with that in a control group without CSCR.Patients and Methods: A 3-month cross-sectional observational and interventional study was conducted involving 40 patients diagnosed with CSCR, divided into two groups: Group A (20 patients with recurrent CSCR) and Group B (20 patients with a single CSCR episode). Both groups were matched with a control group of 40 individuals without CSCR. All participants underwent comprehensive ophthalmologic examinations and optical coherence tomography (OCT) to confirm CSCR. Patients who tested positive for H. pylori received a 14-day standard eradication therapy. Post-treatment, visual acuity was assessed, and potential side effects were monitored.Results: In Group A (recurrent CSCR), 15 out of 20 patients (75%) tested positive for H. pylori, while in Group B (single episode), 8 out of 20 patients (40%) tested positive. The control group had a prevalence of H. pylori of 12 out of 40 (30%). The differences in prevalence among the groups were statistically significant: Group A vs Control (p < 0.001), Group B vs Control (p = 0.02), and Group A vs Group B (p = 0.03). Post-treatment evaluation showed improved visual acuity and reduced recurrence rates in Group A patients who received H. pylori eradication therapy. However, some side effects associated with the treatment were also reported.Conclusion: The study highlights a significant association between H. pylori infection and central serous chorioretinopathy (CSCR), especially in recurrent cases. Identifying and treating H. pylori in CSCR patients may improve visual outcomes and aid in disease management. However, potential side effects of eradication therapy should be considered.Keywords: Helicobacter pylori, central serous chorioretinopathy, optical coherence tomography